2017
DOI: 10.5152/eurasianjmed.2017.17203
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil Chemokines and Clara Cell Protein 16 Production in Nasal Mucosa of Patients with Persistent Allergic Rhinitis

Abstract: Objective: Eotaxin-2 and regulated on activation normal T cell expressed and secreted (RANTES) are involved in the eosinophil trafficking in patients with persistent allergic rhinitis (PAR). Clara cell protein 16 (CC16) is an anti-inflammatory protein mainly produced by the epithelial non-ciliated Clara cells. The aim of this study was to investigate the production of CC16 and chemokines eotaxin-2 and RANTES in nasal mucosa of patients with PAR.Materials and Methods: Twenty-one PAR patients and 20 healthy part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Our previous investigations showed that inflammation in patients with NPs and allergic rhinitis decreases the levels of CC16 16,23 . We, also, found that the concentration of CC16 in nasal secretions was negatively correlated with the levels of ECP and eotaxin‐2 in patients with NP and perennial allergic rhinitis 16,23,24 . The results of our current study show a negative correlation between CC16 and HSP70, ECP, tryptase, and substance P in nasal secretions, which indicates a significant sensitivity of Clara cells in the nasal respiratory epithelium to a number of pro‐inflammatory mediators that can damage the epithelium.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our previous investigations showed that inflammation in patients with NPs and allergic rhinitis decreases the levels of CC16 16,23 . We, also, found that the concentration of CC16 in nasal secretions was negatively correlated with the levels of ECP and eotaxin‐2 in patients with NP and perennial allergic rhinitis 16,23,24 . The results of our current study show a negative correlation between CC16 and HSP70, ECP, tryptase, and substance P in nasal secretions, which indicates a significant sensitivity of Clara cells in the nasal respiratory epithelium to a number of pro‐inflammatory mediators that can damage the epithelium.…”
Section: Discussionsupporting
confidence: 71%
“…The results of our current study show a negative correlation between CC16 and HSP70, ECP, tryptase, and substance P in nasal secretions, which indicates a significant sensitivity of Clara cells in the nasal respiratory epithelium to a number of pro‐inflammatory mediators that can damage the epithelium. After topical corticosteroid use, the concentrations of CC16 increased in both allergic rhinitis and NP patients, suggesting that CC16 measured in nasal secretions could be a reliable marker for assessment of the recovery function of sinonasal mucosa during local corticosteroid therapy 16,24 …”
Section: Discussionmentioning
confidence: 99%
“…14 Another study reported that the IL-5 concentration in nasal secretion increased by fivefold in patients with AR. 15 In studies that used CC16, the CC16 concentration was lower in patients with persistent AR than in healthy individuals, 16 and the CC16 levels in nasal secretions and the severity of rhinitis symptoms negatively correlated. 17 Our results corresponded to those of the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between local mucosal production of eosinophilic chemokines and CC16 is very important for the development and further control of chronic inflammation. Previous investigations have demonstrated that eotaxins induce stronger transendothelial migration of eosinophils than of other eosinophilic chemokines (17)(18)(19)(20)(21). Shin et al (22) reported inverse correlation between CC16 and eotaxin-2 in the nasal secretion of PAR subjects.…”
Section: The Role Of Cc16 In Ar and Crsmentioning
confidence: 98%
“…In contrast, CC16 inhibits eosinophil chemoattractant and Th2 cytokine (IL-4, IL-5, IL-13) production (23). In other words, there is a dynamic balance between the local production of eotaxin-2 and CC16, which is disturbed in patients with chronic eosinophilic nasal inflammation (21).…”
Section: The Role Of Cc16 In Ar and Crsmentioning
confidence: 99%